Three theoretical perspectives for the study of change in organizations - Acuña A., Eduardo (Estudios de Administración, 1998)
Three theoretical models are presented as a contribution aimed at explaining the occurrence of changes in organizations. The first one is based on the elaborations carried out in the field of organizational development, in which changes are conceived as evolutionary planned processes, with education and participation playing an outstanding role. The second model emphasizes the use of power in the implementation of changes by organizational authorities. This is a suitable strategy in situations where changes are radical and call for prompt execution. The third model defines changes as a result of interactive processes among actors in organizations, who, in accordance with their specific interests, use power to exert influence on the contents and progress of changes. The three models contribute to the development of a theory of organizational change and are framed in an explanatory complementarity. They are also useful for the purposes of praxis in the field of organizational changes.